Relationship between inbreeding and milk production traits in two Italian dairy sheep breeds. (14th October 2022) - Cesarani, Alberto; Mastrangelo, Salvatore; Congiu, Michele; Portolano, Baldassare; Gaspa, Giustino; Tolone, Marco; Macciotta, Nicolò P. P.
Abstract: The effects of inbreeding in livestock species breeds have been well documented and they have a negative impact on profitability. The objective of this study was to evaluate the levels of inbreeding in Sarda (SAR, n  = 785) and Valle del Belice (VdB, n  = 473) dairy sheep breeds and their impact on milk production traits. Two inbreeding coefficients ( F ) were estimated: using pedigree ( F PED ), or runs of homozygosity (ROH; F ROH ) at different minimum ROH lengths and different ROH classes. After the quality control, 38, 779 single nucleotide polymorphisms remained for further analyses. A mixed‐linear model was used to evaluate the impact of inbreeding coefficients on production traits within each breed. VdB showed higher inbreeding coefficients compared to SAR, with both breeds showing lower estimates as the minimum ROH length increased. Significant inbreeding depression was found only for milk yield, with a loss of around 7 g/day (for SAR) and 9 g/day (VdB) for a 1% increase of F ROH . The present study confirms how the use of genomic information can be used to manage intra‐breed diversity and to calculate the effects of inbreeding on phenotypic traits.